2017
DOI: 10.1016/j.kjms.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of genes encoding resistance to aminoglycoside modifying enzymes in methicillin‐resistant Staphylococcus aureus (MRSA) strains

Abstract: Today Methicillin-Resistant Staphylococcus aureus (MRSA) have acquired multiple resistance to a wide range of antibiotics including aminoglycosides. So, this study was aimed to investigate the rate of aminoglycoside resistance and the frequency of aminoglycoside resistance mediated genes of aac(Ia)-2, aph(3)-IIIa and ant(4')-Ia among MRSA strains. A total of 467 staphylococci isolates were collected from various clinical samples. S. aureus strains were identified by standard culture and identification criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 25 publications
4
39
2
Order By: Relevance
“…16 A previous study on MRSA in Khuzestan province revealed a dramatic annual increase in the proportion of isolates resistant to methicillin during the recent years, rising from 60% in 2017 and 2018 to a peak of 77% in 2019. [19][20][21][22] Such differences in the prevalence of MRSA infections in our region might reflect the fact that in these areas, different policies are considered for infection control and other factors. 23 There is a continuous increase in the global prevalence of MRSA in European countries.…”
Section: Discussionmentioning
confidence: 99%
“…16 A previous study on MRSA in Khuzestan province revealed a dramatic annual increase in the proportion of isolates resistant to methicillin during the recent years, rising from 60% in 2017 and 2018 to a peak of 77% in 2019. [19][20][21][22] Such differences in the prevalence of MRSA infections in our region might reflect the fact that in these areas, different policies are considered for infection control and other factors. 23 There is a continuous increase in the global prevalence of MRSA in European countries.…”
Section: Discussionmentioning
confidence: 99%
“…this is higher than 47.8% previously reported in Iran [40]. A resistance rate of 84.5% reported in the Sub Himalayan Region of India [41], reflects and increasing resistance nature of MRSA towards aminoglycosides. Similarly, the report indicates Tetracycline resistance rate of 80.7%, which is much higher than previous reports from Tehran (61%) [42].…”
Section: Discussionmentioning
confidence: 52%
“…Therapeutic approaches in patients with severe burns requires use of antibacterial drugs [18][19][20]. Opportunistic microorganisms such as S. aureus, which are the leading causative agents of opportunistic infections, are an important problem nowadays as these microorganisms developed resistance to methicillin [21] and some other antibiotics such as aminoglycosides and tetracyclines due to their uncontrolled used in medicine [1,2,4,12,13]. In such conditions analytical mathematical prediction of the susceptibility level based on the data from dynamic microbiological investigation of the S. aureus susceptibility to staphylococci and doxycycline is considered important in the effective assessment of the feasibility of alternative use of these drugs in patients with severe burns [14].…”
Section: Discussionmentioning
confidence: 99%
“…Despite exponential decrease of the S. aureus susceptibility in 2014-2017 predictive curve indicated an increase of susceptibility in the nearest future. Determined differences in the predicted tendencies of S. aureus susceptibility to various aminoglycosides can be in the directly dependent on the genetically predetermined mechanisms of different resistance genes expression by the microorganism to the drugs of this group [12,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation